Analysis of the Substrate Specificity of the SMYD2 Protein Lysine Methyltransferase and Discovery of Novel Non‐Histone Substrates. (29th October 2019) - Weirich, Sara; Schuhmacher, Maren Kirstin; Kudithipudi, Srikanth; Lungu, Cristiana; Ferguson, Andrew D.; Jeltsch, Albert
Abstract: The SMYD2 protein lysine methyltransferase methylates various histone and non‐histone proteins and is overexpressed in several cancers. Using peptide arrays, we investigated the substrate specificity of the enzyme, revealing a recognition of leucine (or weaker phenylalanine) at the −1 peptide site and disfavor of acidic residues at the +1 to +3 sites. Using this motif, novel SMYD2 peptide substrates were identified, leading to the discovery of 32 novel peptide substrates with a validated target site. Among them, 19 were previously reported to be methylated at the target lysine in human cells, strongly suggesting that SMYD2 is the protein lysine methyltransferase responsible for this activity. Methylation of some of the novel peptide substrates was tested at the protein level, leading to the identification of 14 novel protein substrates of SMYD2, six of which were more strongly methylated than p53, the best SMYD2 substrate described so far. The novel SMYD2 substrate proteins are involved in diverse biological processes such as chromatin regulation, transcription, and intracellular signaling. The results of our study provide a fundament for future investigations into the role of this important enzyme in normal development and cancer. Abstract : SMYD2 methylates different histone and non‐histone proteins. We investigated its substrate specificity and discovered several novel peptide and protein substrates, many of which are methylated more strongly than the p53 protein, the best SMYD2 substrate described so far. Our data will aid in understanding the role of SMYD2 in development and cancer.